KEMAMPUAN PROSES DAN KARAKTERISTIK VULKANISASI CAMPURAN NBR/EPDM - hesty eka mayasari; Ike Setyorini; Noor Maryam Setyadewi (Balai Riset dan Standardisasi Industri Palembang, 2018)
Blending of two rubbers can produce superior product properties. This study examines the process and cure characteristics of the NBR/EPDM blend. This study used several types of compatibilizer, i.e. methyl-methacrylate-butadiene-stirene (MBS), montmorillonite, and silica. Compatibilizer is used to get the homogeneous blend. NBR/EPDM compounds were done by two-roll mill. The mooney viscosity, rheology, and cure kinetics were studied with mooney viscometer and rheometer. It is known that the NBR/EPDM blends produce the compound with the process ability, curing time, and cure rate index better than NBR compound and EPDM compound separately. Montmorillonite as the compatibilizer produces compound with the process ability and cure rate index better than MBS and silica. Montmorillonite can be used as appropriate compatibilizer for the NBR/EPDM blend.